Analysis of loss to follow-up in 4099 multidrug-resistant pulmonary tuberculosis patients. Issue 1 (11th July 2019) - Walker, Ian F.; Shi, Oumin; Hicks, Joseph P.; Elsey, Helen; Wei, Xiaolin; Menzies, Dick; Lan, Zhiyi; Falzon, Dennis; Migliori, Giovanni Battista; Pérez-Guzmán, Carlos; Vargas, Mario H.; García-García, Lourdes; et al.
Loss to follow-up (LFU) of ≥2 consecutive months contributes to the poor levels of treatment success in multidrug-resistant tuberculosis (MDR-TB) reported by TB programmes. We explored the timing of when LFU occurs by month of MDR-TB treatment and identified patient-level risk factors associated with LFU. We analysed a dataset of individual MDR-TB patient data (4099 patients from 22 countries). We used Kaplan–Meier survival curves to plot time to LFU and a Cox proportional hazards model to explore the association of potential risk factors with LFU. Around one-sixth (n=702) of patients were recorded as LFU. Median (interquartile range) time to LFU was 7 (3–11) months. The majority of LFU occurred in the initial phase of treatment (75% in the first 11 months). Major risk factors associated with LFU were: age 36–50 years (HR 1.3, 95% CI 1.0–1.6; p=0.04) compared with age 0–25 years, being HIV positive (HR 1.8, 95% CI 1.2–2.7; p<0.01) compared with HIV negative, on an individualised treatment regimen (HR 0.7, 95% CI 0.6–1.0; p=0.03) compared with a standardised regimen and a recorded serious adverse event (HR 0.5, 95% CI 0.4–0.6; p<0.01) compared with no serious adverse event. Both patient- and regimen-related factors were associated with LFU, which may guide interventions to improve treatment adherence, particularly in the first 11 months. Globally, 75% of loss to follow-up occurs in the first 11 months of MDR-TB treatment. Highest risk is HIV positive, age 36–50 years and standardised regimen. http://bit.ly/2GwKcS1